On anachronism: The curious presence of Spheroids and Polyhedrons at Acheulo–Yabrudian Qesem Cave, Israel. (4th April 2016) - Barkai, Ran; Gopher, Avi
Abstract: The Middle Pleistocene site of Qesem Cave is mostly characterized by a plethora of cultural innovations and "Ahead of its time" phenomena (e.g., habitual use of fire; systematic blade production; Quina scrapers; lithic and bone recycling; systematic cooperative hunting; meat roasting, and more). Within such a context of major cultural innovations, a small but significant assemblage of shaped stone balls, mostly described as Spheroids/Polyhedrons, is of note. In this paper we present, for the first time, the stone balls of Qesem Cave and discuss their contextual and spatial patterning. This adds what we perceive as some sort of anachronism to the Acheulo–Yabrudian cultural complex (AYCC) array of human behavior in an important stage of human cultural and biological evolution in the southern Levant.